Association of insomnia and multidimensional frailty in community‐dwelling older adults: A cross‐sectional survey. Issue 1 (29th June 2021) - Fan, Junyao; Liu, Yueting; Wang, Quan; Zhao, Huimin; Kong, Linglin; Li, Jie
Abstract: Objective: To evaluate the relationship between insomnia and multidimensional frailty. Background: Frailty has major implications on adverse health outcomes of older adults. In recent years, multidimensional nature of frailty has been increasingly recognised. Many frail older adults also suffer from insomnia. Methods: This was a cross‐sectional observational study including 454 community‐dwelling adults aged 60 and older. Insomnia was defined as a subjective experience of inadequate sleep duration or quality that affects social functioning during the day, based on the Athens Insomnia Scale (AIS), and multidimensional frailty was based on Tilburg Frailty Indicator (TFI). The STROBE checklist was used to guide the submission. Results: Mean age was 69.1 years old, 211 (46.5%) of participants suffered from insomnia, and 185 (40.7%) of participants were frail. There was a significant relationship between insomnia and multidimensional frailty (physical, psychological and social dimensions). Insomnia was associated with frailty, adjusting for sociodemographic characteristics and comorbidity OR of 6.863 (95% CI: 4.237–11.116). Conclusion: Frailty was independently predicted by insomnia. Future researches should determine whether there is a causal relationship between insomnia and multidimensional frailty, with the ultimate goal of providing interventions to reverse or prevent frailty. Relevance to clinical practice: This study emphasises the importance of assessment and treatment of insomnia, potentially contributing to the reversion and prevention of frailty in community‐dwelling older adults.